Early Post-operative Outcome of Primary Repair of Bladder Exstrophy With or Without Osteotomy (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: Bladder exstrophy (BE) is a variety of infraumbilical midline anterior abdominal wall defect. This rare spectrum of anomalies involves the urinary tract, genital tract, musculoskeletal, system and sometimes the intestinal tract. Surgical reconstruction with or without osteotomy is the treatment of choice for BE. Objective: To evaluate the intersymphyseal gap (ISG) before, during and after operation (pubic diastasis) and to evaluate the status of post-operative wound healing.Materials & Methods: This cross sectional study was conducted on 18 patients of paediatric age group over a period from February 2007 to October 2008 who were admitted with classical bladder extrophy (BE) in the department of paediatric surgery, BSMMU.. They were divided into two groups. In group-A: 8 patients of BE were undergone primary repair with osteotomy and in group-B primary repair done in 10 patients without osteotomy. Results: Two (2) months post-operative follow-up revealed that all osteotomy patients (group- A) developed re-diastasis of pubic symphysis. Statistically no significant difference of ISG was observed in two groups of patients. Wound healing was better in without osteotomy (group-B) patients (80% vs 50%) and wound failure was more in osteotomy patients (50% vs 20%). Moreover, osteotomy group need hospitalization for longer period of time.Conclusions: Although osteotomy is an essential step in the management of BE, this study revealed that it does not improve the early post-operative outcome.DOI: http://dx.doi.org/10.3329/jpsb.v2i2.19546